2019
DOI: 10.1038/s41396-019-0344-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial persistence promotes the evolution of antibiotic resistance by increasing survival and mutation rates

Abstract: Persisters are transiently antibiotic-tolerant cells that complicate the treatment of bacterial infections. Both theory and experiments have suggested that persisters facilitate genetic resistance by constituting an evolutionary reservoir of viable cells. Here, we provide evidence for a strong positive correlation between persistence and the likelihood to become genetically resistant in natural and lab strains of E. coli. This correlation can be partly attributed to the increased availability of viable cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
235
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(280 citation statements)
references
References 78 publications
(118 reference statements)
11
235
0
4
Order By: Relevance
“…1E, t=0). Flow cytometry reveals ongoing cell division as a dilution of GFP, whereas the fluorescence levels are maintained 5 in the nonproliferating subpopulation ( Fig. 1E, WT at t=2.5 h).…”
Section: Deletion Of Crp and Cyaa Reduced Non-growing Cell Levels Inmentioning
confidence: 99%
See 1 more Smart Citation
“…1E, t=0). Flow cytometry reveals ongoing cell division as a dilution of GFP, whereas the fluorescence levels are maintained 5 in the nonproliferating subpopulation ( Fig. 1E, WT at t=2.5 h).…”
Section: Deletion Of Crp and Cyaa Reduced Non-growing Cell Levels Inmentioning
confidence: 99%
“…Persisters are an important health problem, because they are thought to underlie the propensity of recurrent infections to relapse [2][3][4] and serve as a reservoir from which drug-resistant mutants can emerge [5][6][7][8] . Persisters exhibit a diverse range of proliferative, metabolic, and transcriptional activities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that mutations conferring antibiotic tolerance or persistence promote the evolution of antibiotic resistance 21,22 . Moreover, tolerance mutations can 1) interact synergistically with resistance mutations to increase bacterial survival during antibiotic treatment 23 and 2) promote the establishment of resistance mutations during combination drug therapy 24 .…”
Section: Pyocyanin Promotes the Evolution Of Antibiotic Resistancementioning
confidence: 99%
“…Firstly, in studies involving long exposure of Mycobacterium tuberculosis to rifampin, Sebastian and colleagues concluded that persisters are a source of de novo resistant mutants [26]; secondly, Balaban and colleagues observed that the evolution of increased tolerance or persistence confer mutations in E. coli populations under intermittent ampicillin exposure [27]. In 2019, Windels and colleagues discovered a strong, positive correlation between persister levels and the probability of resistance evolving in natural isolates and laboratory strains of E. coli [28]. Although different types of antibiotics and different experimental conditions were used in these three studies, the results are consistent, strongly suggesting a widespread link between persistence/tolerance to antibiotics and the evolution of resistance to these drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Although different types of antibiotics and different experimental conditions were used in these three studies, the results are consistent, strongly suggesting a widespread link between persistence/tolerance to antibiotics and the evolution of resistance to these drugs. Considerable efforts should hereafter be devoted to the development of strategies that can eliminate tolerant and persistent cells, which potentially favor the evolution of resistance [28].…”
Section: Introductionmentioning
confidence: 99%